Optimal Placement of Distributed Generations in Radial Distribution Systems Using Various PSO and DE Algorithms - Manafi, H.; Ghadimi, N.; Ojaroudi, M.; Farhadi, P. (Elektronika ir elektrotechnika, 2013)
Distributed generations (DGs) have been continuously integrating into the distribution systems. Size and site of distributed generations have significant impacts on the system real power losses reduction and voltage profile improvement in the radial distribution systems. In this paper, recent and more dynamic PSO as well as improved DE algorithms are used for optimum placement of distributed generations in radial distribution systems. The objective of this paper is to minimize distribution system real power losses by the least possible injected power from distributed generations. To assess different PSO and DE algorithms capabilities, simulations carried out on two IEEE 33-bus and 69-bus standard radial distribution systems. DOI: http://dx.doi.org/10.5755/j01.eee.19.10.1941